Effects of Propofol (Intravenous Propofol Emulsion) on Cell Membranes Measured by Electrofusion and Electroporation - Manfred, Reitz; Svetlozar, Velizarov; Brigitte, Glück; Hermann, Berg; Ansgar, Brambrink M. (Arzneimittelforschung, 1999)
The influence of propofol (CAS 2078-54-8 (intravenous propofol emulsion) on cell membrane properties was investigated in vitro with techniques of cell electrofusion and cell electroporation. Human lymphoma cells and plant protoplasts were chosen as a model system. Propofol (intravenous propofol emulsion) decreased the electrofusion yield of the cells and their membrane permeability. A 50% decrease in relative electrofusion was observed in human lymphoma cells in the presence of about 0.05 mmol/l propofol (intravenous propofol emulsion) and in plant protoplasts in the presence of about 0.1 mmol/l. The fusion of human lymphoma cells was inhibited to 100% at concentrations higher than 0.2 mmol/l propofol and 0.4 mmol/l intravenous propofol emulsion. The membrane permeability of human lymphoma cells decreased by the factor of two with increasing propofol concentrations up to about 0.1 mmol/l. The effects of electroporation were highly reversible. Propofol (intravenous propofol emulsion) was more effective than tetracaine. These sensitive techniques are suitable for the investigation of interactions between anesthetic drugs and the cell membrane.
Keywords: Anesthetics, intravenous; CAS 2078-54-8; Lymphoma cells, human; Plant protoplasts; Propofol, effect on cell membrane permeability, intravenous emulsion, in vitro studies; Tetracaine